the FIRST BREEDING RECORD OF ASIAN EMERALD DOVE CHALCOPAPS INDICA (COLUMBIFORMES: COLUMBIDAE) IN BANGKA ISLAND, SUMATRA - Iqbal, Muhammad; Cindy Asyavira, Gita; Komala Sari, Diah (CONSERVA, 2025)
This paper reports the first documented breeding record of the Emerald Dove Chalcophaps indica on Bangka Island, Sumatra, Indonesia. On 9 December 2024, We conducted a nocturnal fauna survey in Kemuja village and discovered an C. indica sitting on a nest approximately one meter above the ground in a remnant heath forest surrounded by rubber plantations. This finding confirms that the C. indica breeds on Bangka Island and highlights the importance of continued research into the species' ecology and conservation status. The discovery also underscores the adaptability of the C. indica to human-modified landscapes and emphasizes the need for conservation efforts to preserve habitats that support the species' breeding activities.